2021
DOI: 10.1038/s41380-021-01096-z
|View full text |Cite
|
Sign up to set email alerts
|

FXR1 regulation of parvalbumin interneurons in the prefrontal cortex is critical for schizophrenia-like behaviors

Abstract: Parvalbumin interneurons (PVIs) are affected in many psychiatric disorders including schizophrenia (SCZ), however the mechanism remains unclear. FXR1 , a high confident risk gene for SCZ, is indispensable but its role in the brain is largely unknown. We show that deleting FXR1 from PVIs of medial prefrontal cortex (mPFC) leads to reduced PVI excitability, impaired mPFC gamma oscillation, and SCZ-like behaviors. PVI-specific translational profiling reveals that FXR1 regulates the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 92 publications
0
20
0
Order By: Relevance
“…Variants in FXR1 have been associated with several neuropsychiatric diseases, notably insomnia, bipolar disorder and schizophrenia 11 12. In addition, differential expression of FXR1 was reported in patients with schizophrenia 13. All three patients from family D had significant psychiatric manifestations (depression, bipolar disorder, social anxiety disorder, generalised anxiety disorder, attention deficit disorder, bulimia); however, the association of psychiatric manifestations with FXR1 pathogenic variants requires further study.…”
Section: Discussionmentioning
confidence: 98%
“…Variants in FXR1 have been associated with several neuropsychiatric diseases, notably insomnia, bipolar disorder and schizophrenia 11 12. In addition, differential expression of FXR1 was reported in patients with schizophrenia 13. All three patients from family D had significant psychiatric manifestations (depression, bipolar disorder, social anxiety disorder, generalised anxiety disorder, attention deficit disorder, bulimia); however, the association of psychiatric manifestations with FXR1 pathogenic variants requires further study.…”
Section: Discussionmentioning
confidence: 98%
“…Besides neuroimaging studies, genetic studies have indicated mPFC as a potential key region in the pathophysiological mechanisms behind insomnia problems in SCZ. Shen et al found that deleting FXR1 gene, of which the variants are linked to shorter sleep duration 68 , from parvalbumin interneurons of mPFC leads to impaired mPFC gamma oscillation and SCZ-like behaviors 69 . The large GWAS study in 1,331,010 individuals also showed insomnia-related gene set enrichments in frontal cortex, which have correlations with psychiatric traits 70 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have implicated inhibitory neurons in NDDs [ 2 , 3 , 17 , 18 ]. Telencephalic inhibitory neurons are born in the transitory ganglionic eminences (GEs), which are subdivided into three regions—the medial, caudal, and lateral eminences (MGE, CGE, and LGE, respectively) (Fig.…”
Section: The Developing Human Brain In High Resolutionmentioning
confidence: 99%